The forgotten facet: Employee satisfaction with management above the level of immediate supervision - Dalal, Reeshad S. (Institutional Knowledge at Singapore Management University, 2011)
This paper contends that satisfaction with management above immediate supervision is a key component of overall job satisfaction. We demonstrate that early job satisfaction researchers regarded this construct as very important, and that practitioners continue to regard the construct as very important. Yet, the visibility of this construct in current academic research is hampered by the absence of a comprehensive and theoretically based measure of the construct. In the present paper, we define the construct and formulate a nomological network for it. We subsequently describe the development of the Satisfaction with Upper and Middle Management (SUMM) scale, and we assess the validity of its scores via four independent samples. Results support our contention that satisfaction with management should be related to the traditional job satisfaction facets, but also that, because it is the facet of job satisfaction that pertains to the organisation's collective authority system, it should explain incremental variance (beyond these traditional facets) not only in global job satisfaction but also in organisational commitment and organisational justice. Implications and avenues for future research are discussed.